Peningkatan Keterampilan Menangkap Bola Melalui Pendekatan Permainan Bola Tangkap pada Siswa-Siswi Kelas V SD Pakis 8 Surabaya - Iswiharjo, Elung Esa; Dinata, Vega Candra (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this class action research is to improve the ball catching skills of grade V students of SDN 8 Surabaya. The catch-ball method was used in this study. This class action research was carried out in two cycles, with 20 students and female students, 10 male students and 10 female students each. To collect data, observations, skill tests, and documentation are used. The results showed that students' ball-catching skills improved from pre-cycle to second cycle. The average score of students' ball-catching skills is 65.5 with classical completeness of 40%; In the second cycle, the value of the ball-catching skill increased to 82.3 with a classical completeness of 90%. In conclusion, the catchball game method is effective in improving students' ball-catching skills.